Cross-sectional and longitudinal validation of the Slovene version of the health-related quality of life questionnaire in patients with Hymenoptera venom allergy (HRQLH-S) - T. Močnik; J. Šelb; M. Peršolja; M. Košnik (BMC Psychology)
Abstract Background This study aimed to determine to what degree venom immunotherapy can affect the Quality of Life (QoL) in patients hypersensitive to the Hymenoptera venom and to validate the Slovene version of the “Vespid Allergy Quality of Life Questionnaire.” Methods The “Vespid Allergy Quality of Life Questionnaire” (VQLQ), developed by Oude Elberink et al., has become a well-established diagnostic instrument. The Slovene version of the Health-Related Quality of Life Questionnaire for Hymenoptera venom allergy (HRQLH-S) was administered to 288 patients from different groups with a confirmed diagnosis of Hymenoptera venom hypersensitivity to achieve cross-sectional validation. The HRQLH-S results were compared among groups, with an Expectation of Outcome (EoO) questionnaire and a 10-point Likart scale question: (How much is your QoL reduced by being allergic to insect sting?). The questionnaire was administered to 49 patients treated with venom immunotherapy to establish longitudinal validity. Results In cross-sectional study, statistically significant differences (p < 0.001) were observed in patients treated with venom immunotherapy compared to untreated patients. The median (Mdn) was used to compare the groups. Patients that have already been treated recorded a rise in QoL only six months into treatment (Mdn = 3.18), compared to the untreated (Mdn = 4.20). Further noticeable improvements in the QoL were recorded in patients treated for three to five years (Mdn = 2.47). Statistically significant correlations between the HRQLH-S results and the EoO were confirmed in cases of patients with wasp venom hypersensitivity (Q15r = 0.82; Q16r = 0.67; Q17r = 0.63; p < 0.001) and those with honeybee venom hypersensitivity (Q15r = 0.79; Q16r = 0.62; Q17r = 0.64; p < 0.001). The cross-sectional validation yielded a correlation coefficient of 0.96 (Cronbach α). In the longitudinal validation, we showed a significant correlation between EoO and HRQLH-S (Q15r = 0.87; Q16r = 0.77; Q17r = 0.71; p < 0.000.1), with a good internal consistency (Cronbach α = 0.97). Furthermore, we found a significant difference (p < 0.001) in the QoL of pretreatment patients (Mdn = 3.91) compared to the value after five years of treatment (Mdn = 2.06). Conclusions Results confirm the efficiency of VIT on QoL in patients with Hymenoptera venom hypersensitivity. The HRQLH-S questionnaire proved suitable for measuring QoL in wasp and honeybee venom-allergic patients.